Serious Games in Physical Rehabilitation From Theory to Practice - Bonnechère, Bruno (Springer International Publishing, 2018)
Marketing text: This innovative book explores how games can be serious, even though most people generally associate them with entertainment and fun. It demonstrates how videogames can be a valuable tool in clinics and demonstrates how clinicians can use them in physical rehabilitation for various pathologies. It also describes step by step their integration in rehabilitation, from the (gaming) technology used to its application in clinics. Further, drawing on an extensive literature review, it discusses the pros and cons of videogames and how they can help overcome certain obstacles to rehabilitation. The last part of the book examines the main challenges and barriers that still need to be addressed to increase and improve the use and efficacy of this new technology for patients. The book is intended for physiotherapists and clinicians alike, providing a useful tool for all those seeking a comprehensive overview of the field of serious games and considering adding it to conventional rehabilitation treatment.